Flow Modeling in an Evaporator of a Nonconventional Energetic System - Kovalcik, Andrej; Toporcer, Emil; Hlavna, Vladimir (Communications - Scientific letters of the University of Zilina, 2011)
An alternative cooling medium (lithium bromide liquid) flows in a cooling jacket of a combustion engine of a nonconventional energetic unit. The paper deals with a flow simulation of the working medium in the vaporization container of a cooling circuit of the nonconventional combustion engine. Consequently evaporation and thermal states at the atmospheric pressure above the nonconventional cooling liquid (solution LiBr – H2O) level in the evaporator are simulated. Limiting conditions for the functionality assurance of the cooling system of the nonconventional combustion engine were found by means of a simulation.